Oxidation of p,p'-DDT and p,p'-DDE in highly and long-term contaminated soil using Fenton reaction in a slurry system - Dalla Villa, Ricardo; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier B.V., 2006)
The degradation of DDT [1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane] and DDE [2,2-bis(4-chlorophenyl)-1,1-dichloroethylene] in highly and long-term contaminated soil using Fenton reaction in a slurry system is studied in this work. The influence of the amount of soluble iron added to the slurry versus the mineral iron originally present in the soil, and the influence of H2O2 concentration on the degradation process are evaluated. The main iron mineral species encountered in the soil, hematite (Fe2O3), did not show catalytic activity in the decomposition of H2O2, resulting in low degradation of DDT (24%) and DDE (4%) after 6 h. The addition of soluble iron (3.0 mmol L-1) improves the reaction reaching 53% degradation of DDT and 46% of DDE. The increase in iron concentration from 3.0 to 24 mmol L-1 improves slightly the degradation rate of the contaminants. However, similar degradation percentages were obtained after 24 h of reaction. It was observed that low concentrations of H2O2 were sufficient to degrade around 50% of the DDT and DDE present in the soil, while higher degradation percentages were achieved only with high amounts of this reagent (1.1 mol L-1). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Fenton; DDT; soil remediation